2004
DOI: 10.1128/aem.70.4.2271-2278.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Chloride Reduces Production of Curvacin A, a Bacteriocin Produced by Lactobacillus curvatus Strain LTH 1174, Originating from Fermented Sausage

Abstract: Lactobacillus curvatus LTH 1174, a strain originating in fermented sausage, produces the antilisterial bacteriocin curvacin A. Its biokinetics of cell growth and bacteriocin production as a function of various concentrations of salt (sodium chloride) were investigated in vitro during laboratory fermentations using modified MRS medium. A model was set up to describe the effects of different NaCl concentrations on microbial behavior. Both cell growth and bacteriocin activity were affected by changes in the salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 64 publications
(67 reference statements)
4
32
0
Order By: Relevance
“…The equations used are listed in Table 1. They are the same as those reported by Messens et al (32), except that bacteriocin production was made dependent on a value of X B , i.e., the minimum biomass concentration required for the onset of bacteriocin production due to induction (11,28,42).…”
Section: Methodsmentioning
confidence: 58%
“…The equations used are listed in Table 1. They are the same as those reported by Messens et al (32), except that bacteriocin production was made dependent on a value of X B , i.e., the minimum biomass concentration required for the onset of bacteriocin production due to induction (11,28,42).…”
Section: Methodsmentioning
confidence: 58%
“…Briefly, the amount of lactic acid produced and the residual glucose concentration were determined by high-performance liquid chromatography (9), and the level of soluble bacteriocin activity in the cell-free culture supernatant was determined by a modified critical dilution method with L. innocua LMG 13568 as the indicator organism (9,24). The twofold critical dilution method displays a variation coefficient of 20% on measurement but has repeatedly been shown to yield good overall reproducibility of the bacteriocin activity curve of L. curvatus LTH 1174 (47). The presence of spices did not interfere with the bacteriocin activity assay.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it was shown that these large-scale and strictly computer-controlled fermentation experiments are highly repeatable, as well as the estimation of the biokinetic parameters for a defined set of fermentation conditions. Based on repetitions, it was estimated for the bacteriocin-producing strains L. sakei CTC 494 and L. curvatus LTH 1174 that the coefficients of variation of the biokinetic parameters used for modeling are generally lower than 10%, with the exception of k inact , for which variation of up to 25% can be observed (24,47). Moreover, inherent biological variation within a treatment was small compared to the large differences observed among fermentation experiments under different conditions.…”
Section: Methodsmentioning
confidence: 99%
“…P. acidilactici QC38 was inoculated (1% v/v) into MRS broth containing different concentrations of NaCl (from 0.5-10% w/v) and incubated at 37°C during 24 h. The optical density at 600 nm wavelength was measured to evaluate bacterial growth in the broth culture. Production of bacteriocin in each concentration of NaCl was evaluated by the AWDA assay using L. monocytogenes as the indicator of inhibition (Verluyten et al, 2004).PCR of bacteriocin gene. Plasmid DNA isolation was performed by the modified alkaline lysis method (Anderson and McKay, 1983) and DNA was used as a template for the amplification of bacteriocin gene.…”
mentioning
confidence: 99%